Acute Rheumatic Fever Presenting With Isolated Myocarditis and Right Coronary Artery Occlusion - Sumedh Iyengar; Md. Mashiul Alam; Evgeny Shkolnik; Stuart Zarich (Annals of Internal Medicine: Clinical Cases)
Acute rheumatic fever (ARF) traditionally presents with carditis, usually involving valvulitis. This case report describes a 22-year-old man with an atypical ARF presentation: isolated myocarditis and coronary artery occlusion. He presented with chest pain and signs of cardiogenic shock. Initial electrocardiogram and elevated cardiac biomarkers led to a diagnosis of acute myocardial infarction due to 100% right coronary artery occlusion, which was managed with wire-based thrombus removal. Further work-up revealed elevated antistreptolysin-O titers and cardiac magnetic resonance imaging consistent with myocarditis. This case highlights an occurrence of such an unusual presentation of ARF.